Schaum's outline of introduction to probability and statistics - Lipschutz, Seymour; Schiller, John J. (Schaum's outline series, 2012)
SCHAUM'S INTRODUCTION TO PROBABILITY AND STATISTICS fits all probability/statistics courses. It features hundreds of solved problems for practice, and its calculus-free, outline format appeals especially to the nontechnically minded. 90 illustrations